Cyclization assisted iterative growth method for synthesizing monodisperse polymers. (December 2022) - Liu, Xianfeng; Ren, Xiangzhu; Li, Xijuan; Zhang, Yu; Wu, Ying; Zhang, Ke
Abstract: A fast iterative growth method is reported to prepare monodisperse polymers assisted by a cyclization technique. This novel method uses a di-functional and a tri-functional compounds as monomer pairs. The di-functional monomer is designed to have an azide and a hydroxyl end groups, while the tri-functional monomer is designed to have an alkyne and a sym-dibenzo-1, 5-cyclooctadiene-3, 7-diyne containing two strained alkynes. One iterative cycle of this novel method is composed by four step reactions. First, the self-accelerating double-strain-promoted azide-alkyne click reaction is used to couple two monomers/oligomers having an azide and a hydroxyl end group pairs with one tri-functional monomer by reacting the azide and strained alkyne groups. This coupling reaction increases chain length and produces an elongated oligomers having two hydroxyl end groups and one alkyne group in the middle position of main-chain. Second, the esterification between anhydride and hydroxyl is used to modify the hydroxyl end groups to endow the elongated oligomers with two azide end groups. Third, copper(I)-catalyzed azide-alkyne click reaction is then used to ring-close the elongated oligomers by reacting the middle alkyne and one terminal azide groups to prepare a tadpole-shaped oligomers with one azide end group. Fourth, the 2, 3-dichloro-5, 6-dicyano-p-benzoquinone oxidized deprotection reaction is used to cleave the preset methoxybenzyl ether bond in the ring of the tadpole-shaped oligomers and rebuild an azide and a hydroxyl end group pairs for the elongated oligomers. The repetition of above iterative cycle can synthesize the monodisperse polymers with a fast chain-growth manner of 2 n+1 -1. Graphical abstract: Image, graphical abstract